MLSSDCNN: Automatic Sentiment Examination Model Creation using Multi Domain Light Semi Supervised Deep Convolution Neural Network - Manasa K N, M. C. PADMA , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Type Emotional research deliberated at categorizing positive or negative has fascinated more and more consideration in recent years. Traditional methods of emotional categorizing typically work well with labeled data. Transfer training is a popular method to solve problems where the model cannot be applied straight to the target domain in multi-domain emotional categorizing framework. This article intended a transfer learning system derived from the Light Semi Supervised Deep Convolution Neural Network (LSSDCNN). This LSSDCNN build a convolutional neural network model using extracted features moreover distribute the weights among all layers. In this article, LSSDCNN used five broad categories of Linguistic Inquiry and Word Count (LIWC) that includes linguistic and human psychological characteristics. Intellectual Broad Multi Domain Data Transfer Network employs sentences as well as aspects for extracting unique data. Particularly, this network intended to discover general features of multiple domains after that the retrieved aspects information through general features. To find out the predictive performance of proposed MultiDomain Light Semi Supervised Deep Convolution Neural Network (MDLSSDCNN), it is compared with existing sentiment models.